Management of Combined Gingival and Alveolar Fenestration in Maxillary Lateral Incisor: A Report of a Rare Case - Ashwath, Balachandran; Subramoniam, Sundaram; Muthukumaraswamy, Arunachalam (Journal of Orofacial Research, 2013)
Gingival fenestrations are of uncertain etiology having rarely been reported in the dental literature. It seems to have a multifactorial origin and is commonly associated with the anterior region of the arch, especially the incisors. They are usually associated with chronic periapical inflammation. The resorption of bone is usually not associated with such defects. The routine therapeutic modalities used for these defects include mucogingival procedures such as free gingival graft,subepithelial connective tissue graft, pouch and tunnel technique and guided tissue regeneration. The following case describes a rare clinical situation where a gingival fenestration is associated with a large bone defect treated with bone grafting and guided tissue regeneration.